A Novel Approach to Treatment of Conjunctival Cyst Ablation Using Atmospheric Low-Temperature Plasma - Nejat F (Dove Medical Press, 2020)
Farhad Nejat,1 Khosrow Jadidi,1 Shiva Pirhadi,1,2 Seyede-Yasamin Adnani,1 Nazanin-Sadat Nabavi,1 Mohammad Amin Nejat1 1Vision Health Research Center, Semnan University of Medical Sciences, Semnan, Iran; 2Department of Biomedical Engineering, Science and Research Branch, Islamic Azad University, Tehran, IranCorrespondence: Farhad NejatVision Health Research Center, Semnan, IranTel +98 9124014938Email fanejat@yahoo.comPurpose: Introducing a new technique to remove the conjunctival cyst using atmospheric low-temperature plasma (ALTP) and assessing its effectiveness.Patients and Methods: Five eyes with conjunctival cysts were included in this study. The procedure was started by applying a plasma spot on the highest point of the cyst, and then other spots were spirally applied to the base of the cyst to debulk it. The conjunctival cysts were removed using the white handpiece of the plasma generator device (Plexr, GMV s.r.l Grottaferrata, Italy). Refraction, visual acuity, intraocular pressure (IOP), contrast sensitivity (CS), aberrometry, dry eye tests, and ocular surface disease index (OSDI) questionnaire were measured before, one and six months after treatment.Results: The mean size of the cysts was 3.6 mm (range 2.1 to 4.8 mm). No intraoperative and postoperative complications were observed. Postoperative examinations showed that the patients’ cysts were completely healed and recurrence did not occur. Significant changes in visual parameters, IOP, CS, aberrometry and dry eye tests were not observed in the follow-up periods after treatment compared to before. OSDI score decreased after cyst removal.Conclusion: Our recommended technique using ALTP can be used as a new approach to treating conjunctival cysts. This technique is a simple, office-based, minimally invasive, effective and inexpensive way to remove a cyst.Keywords: ocular surface disorder, conjunctival cyst, atmospheric low-temperature plasma, sublimation, soft surgery